The use of M. Porter's generic strategies in the Turkish apparel industry and strategy proposals for companies - (:unkn) unknown (Ege Universitesi, 2014)
The purpose of this study is to analyze the use of Porter's generic strategies in successful apparel companies and develop strategy proposals for Turkish apparel companies to create an advantage in international markets. A survey has been developed through the sources in literature to gather data in line with this purpose and competitive strategies of the apparel companies in the Top and Next Top 500 Industrial Enterprises ranking made by ISO each year have been analyzed. According to the findings obtained from the analyses, the most common strategy followed by Turkish apparel industry is the general cost leadership strategy. The Top and Next Top 500 rankings of ISO diverge in competitive strategies they follow. The most common competitive strategy followed by Top 500 companies in ISO ranking after the general cost leadership strategy is differentiation strategy.
Keywords: Apparel industry; Competitive strategy; Cost leadership; Differentiation; M. Porter